Avaliação da cinemática tridimensional da escápula e da dor em mulheres com síndrome fibromiálgica submetidas à hidroterapia - Avila, Mariana Arias (2014)
Fibromyalgia Syndrome (FS) is characterized by chronic, intense, widespread and constant pain, and affects functional performance, especially in women, given the changes in the entire musculoskeletal system they present. The tender points, one characteristic of the FS, are present in great number in the cervical and shoulder girdle regions; this may cause changes in the shoulder movement pattern in these patients. However, there is not enough evidence that show how shoulder kinematics might be altered in this population. Another important point already shown is the presence of Myofascial Trigger Points (MTrPs), factors that may cause and perpetuate pain, and have an important role in the transition from local pain to a more generalized pain condition of these patients. The literature points to hydrotherapy as one of the best treatment for FS symptoms, for the pain improvement it provides. However, it is not known how hydrotherapy would be able to alter shoulder kinematic variables, or if hydrotherapy would have effects on active MTrPs inactivation in this population. Hence, this thesis aimed to characterize scapular kinematics of women with FS, and verify if a 16-week hydrotherapy treatment would alter kinematics variables and pain symptoms in these women. For that, three studies were designed: Study 1 Tridimensional scapular motion during arm elevation is altered in women with fibromyalgia, that aimed to characterize tridimensional scapular kinematics of women with FS compared to a control group; Study 2 Tridimensional scapular motion and pain in women with fibromyalgia syndrome: effects of a 16-week group hydrotherapy program, whose aim was to verify possible effects of hydrotherapy on scapular kinematics and pain variables; Study 3 Decrease in the number of active myofascial trigger points and pain associated to hydrotherapy in women with fibromyalgia, which aimed to evaluate the effects of hydrotherapy on the number of active and latent MTrPs, pressure pain threshold and quality of life of women with FS.